(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: Suicide is the act of deliberately killing oneself. Risk factors for suicide include mental disorder, especially depression and neurological disorders, cancer and HIV infection. Suicide remains a significant global health issue, with hanging being one of the most prevalent methods worldwide. Understanding the factors contributing to hanging suicides is crucial for effective prevention efforts. This study aimed to evaluate the factors associated with the use of highly lethal methods for suicide attempts, with a focus on hanging suicides. Materials and methods: A retrospective observational study was conducted at Chittagong Medical College, analyzing 72 cases of hanging suicides. Data on sociodemographic characteristics, psychosocial factors and environmental factors were collected from autopsy reports and medicolegal records. Descriptive statistics, bivariate analysis, and regression analysis were used to analyze the data. Results: Among the study participants, 69.4% were male, with a mean age of 34.2 years. Marital status analysis revealed that 52.8% were married. Unemployment was prevalent among 61.1% of cases. Environmental factors showed that 80.6% of cases occurred indoors, with an equal distribution between day time and night time incidents. Bivariate analysis indicated a significant correlation between marital status and hanging (p < 0.05) and a strong association between unemployment and hanging (p < 0.001). Regression analysis identified unemployment status as a significant predictor of hanging suicides (OR = 2.5, p < 0.01). Conclusion: This study highlights the importance of considering psychosocial and environmental factors in understanding hanging suicides. Targeted interventions addressing unemployment and marital status may help reduce the incidence of hanging suicides and improve suicide prevention efforts. JCMCTA 2025 ; 36 (2) : 141-144